Fejlődési tartalék, vagy elszalasztott lehetőség (A Dél-Dunántúl turizmusa) - Kraftné Somogyi, Gabriella (Tér és Társadalom, 1994)
We can witness the slow withdrawal of the Southem Transdanubian region from the touristic results of the country since 1985, at that time 27.4% of the home and foreign guest nights sold in the public accommodation establishments of Hungary were in the four counties, while in 1992 only 23.4%. Only Zala was capable of producing a change opposite to this trend – in the given period its share in the turnover grew almost double. In the background of the changes on the one hand there are the decline in the popularity of the recreational tourism on Lake Balaton – more exactly the setting of a demand compatible with the levei of the supply –, the lack of apparent renewal in the touristic product supply and in the conditions of reception, the unfavourable accessibility of some areas of the region – Baranya and Tolna –, the geographical closeness of the prolonging Yugoslavian crisis, and, on the other hand, the gradual evaluation of the health and thermal waters, the improving construction of the conditions of reception in connection with them, the situation along the Austrian border and the versatile touristic and cultural roles of the town of Keszthely. An unfavourable factor for the region is the fact that at the same time as the takeover of market economy, the spread of marketing methods in the sector is slow. There is a lack of organisations of non-profit activities, financed by the actors in the tourism sector, also of their cooperative networking. The region has not got an independent organisation specialised in incoming tourism. Based on their former market connections, the companies formed from the previous county tourist boards deal with considerable activity in the field of incoming tourism. The still high rate of the German guests is a consequence of this, among other things. Lacking special supply packages, the demand towards the region is mainly focused on waterside recreation, thus it is highly seasonal. 43-48% of the guest arrivals is concentrated in the three summer months, which limits the regional development of tourism, and its favourable effect on the general development of the region. The supply structure of the traditional touristic centres is ripe for development in the structure of accommodation establishments, the retail trade and catering services, and leisure time facilities. Development should be achieved by the strengthening of the qualitative features, and the development of the services able to satisfy individual needs. This also means that, in the future, the more intensive adjustment of the local natural, artificial, ethnographic, and productive resources related to the touristic products would be desirable and effective. By more effective use, but not abuse of the local resources, the incomes deriving from tourism can be further increased. At the same time the guests can have a more realistic image of the region. Thus we can make the region more popular among the new, value-seeking tourists that are typical of the market currently.